2017
DOI: 10.1016/j.crci.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficient cenosphere supported catalyst for the esterification of n-octanol with acetic acid

Abstract: An efficient heterogeneous acid catalyst was developed using cenospheres, a byproduct of coal-fired thermal power plants by the method of wet impregnation. Catalyst characterization was carried out using various analytical techniques, namely, Fourier transform infrared, X-ray diffraction, field emission gun scanning electron microscopy and Brunauer eEmmetteTeller surface area and surface acidity analysis. The characterization revealed the excellent catalytic activity of the catalyst for the esterification reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Cenospheres, present in fly ash, are hollow particles of about 10-1000 µm in diameter, with a density lower than 1 g/cm 3 [5]. These could become catalyst supports for certain chemical processes that require high thermal stability [6,7]. Cenospheres are composed of a mixture of aluminosilicates with some amount of K, Ca, Fe, Mg, and a small addition of Ti, Na, P, S, and trace elements [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cenospheres, present in fly ash, are hollow particles of about 10-1000 µm in diameter, with a density lower than 1 g/cm 3 [5]. These could become catalyst supports for certain chemical processes that require high thermal stability [6,7]. Cenospheres are composed of a mixture of aluminosilicates with some amount of K, Ca, Fe, Mg, and a small addition of Ti, Na, P, S, and trace elements [7].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high amount of Al 2 O 3 (23%-33%) and the fact that they were formed at temperatures over 1200 • C, cenospheres have high mechanical and thermal strength, and thus have potential applications in many branches of industry [8]. Cenospheres were examined and have exhibited positive results as catalysts, for example, for esterification of n-octanol with acetic acid [6], for deNOx processes [9], as well as in practical uses in the degradation of pollutants or for water cleanup [10]. Additionally, it was concluded that when used as catalysts, they can show high conversion and selectivity for some important organic reactions under solvent-free conditions [11].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous applications of such material that have been recently studied e.g. cement-based composites [4], particulate reinforced metal matrix composites [5], polymer composites [6][7][8][9], a catalytic support [10][11][12][13] or a fluidised bed material [14][15][16][17]. The main reason for the applying of cenospheres in the composites is to reduce their weight and manufacturing cost, as well as to improve their properties e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of environmental sustainability, heterogeneous catalysts such as ion-exchange resins [4], zeolites [5], ionic liquids [6,7], fly ash cenospheres [8], enzymes [9], Brønsted acids [10,11], and Lewis acids [12,13] were investigated. Apart from these reports, studies related to application of waste materials for the development of efficient catalysts are present in the literature.…”
Section: Introductionmentioning
confidence: 99%